Low levels of tissue inhibitor of metalloproteinase-2 at birth may be associated with subsequent development of bronchopulmonary dysplasia in preterm infants - Choae Lee; Jaewoo An; Ji Hee Kim; Eun Sun Kim; Soo Hyun Kim; Yeon Kyung Cho; Dong Hyun Cha; Man Yong Han; Kyu Hyung Lee; Youn Ho Sheen (Korean Pediatric Society, 2015)
PurposeBronchopulmonary dysplasia (BPD) is characterized by inflammation with proteolytic damage to the lung extracellular matrix. The results from previous studies are inconsistent regarding the role of proteinases and antiproteinases in the development of BPD. The aim of the present study was to investigate whether matrix metalloproteinase (MMP)-8, MMP-9, tissue inhibitor of metalloproteinase (TIMP)-2, and TIMP-1 levels in the serum of preterm infants at birth are related to the development of BPD.MethodsSerum was collected from 62 preterm infants at birth and analyzed for MMP-8, MMP-9, TIMP-2, and TIMP-1 by using enzyme-linked immunosorbent assay. MMPs and TIMPs were compared in BPD (n=24) and no BPD groups (n=38). Clinical predictors of BPD (sex, birth weight, gestational age, etc.) were assessed for both groups. The association between predictors and outcome, BPD, was assessed by using multivariate logistic regression.ResultsSex, birth weight, and mean gestational age were similar between the groups. BPD preterm infants had significantly lower TIMP-2 levels at birth compared with no BPD preterm infants (138.1±23.0 ng/mL vs. 171.8±44.1 ng/mL, P=0.027). No significant difference was observed in MMP-8, MMP-9, and TIMP-1 levels between the two groups. Multivariate logistic regression analysis indicated that the TIMP-2 levels were predictive of BPD after adjusting for sex, birth weight, gestational age, proteinuric preeclampsia, and intraventricular hemorrhage (β=-0.063, P=0.041).ConclusionLow TIMP-2 serum levels at birth may be associated with the subsequent development of BPD in preterm infants.